2022
DOI: 10.1021/acs.analchem.2c04391
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Extracellular Vesicles Based on Surface Glycan Structures by Spongy-like Separation Media

Abstract: Extracellular vesicles (EVs) are lipid bilayer vesicles that enclose various biomolecules. EVs hold promise as sensitive biomarkers to detect and monitor various diseases. However, they have heterogeneous molecular compositions. The compositions of EVs from identical donor cells obtained using the same purification methods may differ, which is a significant obstacle for elucidating objective biological functions. Herein, the potential of a novel lectin-based affinity chromatography (LAC) method to classify EVs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…However, the amount of NPs collected from the culture supernatant was much less than that of the LNPs we had expected. SEVs have membrane proteins such as CD9 and CD81 on their surface, which may cause nonspecific adsorption to the hydrophobic surface of TiO 2 –SPM. , Additionally, because these proteins may cover the phospholipids on the SEV surface, hybridized TiO 2 might require a longer adsorption time to SEVs than that of LNPs. In previous reports, incubation took 5 min until sufficient binding between SEVs in urine and TiO 2 particles was confirmed .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the amount of NPs collected from the culture supernatant was much less than that of the LNPs we had expected. SEVs have membrane proteins such as CD9 and CD81 on their surface, which may cause nonspecific adsorption to the hydrophobic surface of TiO 2 –SPM. , Additionally, because these proteins may cover the phospholipids on the SEV surface, hybridized TiO 2 might require a longer adsorption time to SEVs than that of LNPs. In previous reports, incubation took 5 min until sufficient binding between SEVs in urine and TiO 2 particles was confirmed .…”
Section: Resultsmentioning
confidence: 99%
“…Here, we developed a novel method for purification of SEVs using a highly permeable spongy-like monolithic polymer (spongy-monolith; SPM) hybridized with titanium oxide (TiO 2 ) by thermal mixing (Figure ). SPM provides a flow path suitable for low-pressure chromatographic separation of SEVs without clogging due to its μm-sized through-pores that are much larger than the diameter of SEVs . In addition, SPM consists of poly­(ethylene- co -glycidyl methacrylate) (PEGM), a flexible and inexpensive polymer, applied to separation media with various shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a previous example, we selectively adsorbed and desorbed IgG toward the SPM immobilized protein A by controlling the pH . Furthermore, we successfully separated the extracellular vesicles, exosome, due to the difference in the surface sugar chains using lectin-immobilized SPMs . The study showed that SPM provided the effective separation for bio-related nanoparticles compared to typical porous particle adsorbents.…”
Section: Introductionmentioning
confidence: 93%
“…32 Furthermore, we successfully separated the extracellular vesicles, exosome, due to the difference in the surface sugar chains using lectin-immobilized SPMs. 34 The study showed that SPM provided the effective separation for bio-related nanoparticles compared to typical porous particle adsorbents. According to our studies, paying attention to the spike protein of SARS-CoV-2 that protrudes on the surface of the virus, we conceived that immobilizing an anti-spike protein (AS) binding the spike protein RBD to the SPM selectively adsorbs and desorbs SARS-CoV-2.…”
Section: ■ Introductionmentioning
confidence: 93%